Mono-Alkylated Ligands Based on Pyrazole and Triazole Derivatives Tested Against Fusarium oxysporum f. sp. albedinis: Synthesis, Characterization, DFT, and Phytase Binding Site Identification Using Blind Docking/Virtual Screening for Potent Fophy Inhibitors - Kaddouri, Yassine; Abrigach, Farid; Ouahhoud, Sabir; Benabbes, Redouane; El Kodadi, Mohamed; Alsalme, Ali; Al-Zaqri, Nabil; Warad, Ismail; Touzani, Rachid (Frontiers in Chemistry, 2020)
Twelve recent compounds, incorporating several heterocyclic moieties such as pyrazole, thiazole, triazole, and benzotriazole, made in excellent yield up to 37–99.6%. They have tried against Fusarium oxysporum f. sp. albedinis fungi (Bayoud Disease) where the choicest results are for the compounds 2, 4 and 5 with IC50 = 18.8–54.4 µg/mL. Density functional theory (DFT) study presented their molecular reactivity, while the docking simulations to describe the synergies between the trained compounds of dataset containing all the tested compounds (131 molecules) and F. oxysporum Phytase domain (Fophy) enzyme as biological target. By comparing the results of the docking studies for the Fophy protein, it is found that the compound 5 has the best affinity followed by the compounds 2 and 4, so there is good agreement with the experimental results where their IC50 values are following the order : 74.28 (5) < 150 (2) < 214.10 (4), using Blind docking/virtual screening of the homology modelled protein and two different tools as Autodock Vina and Dockthor webtool that gave us predicted sites for further antifungal drug design.